PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP PENINGKATAN PEMBANGUNAN EKONOMI MASYARAKAT (Studi di Desa Koreng Kecamatan Tareran Kabupaten Minahasa Selatan) - KAWUNG, STASIA HELLEN; POSUMAH, JOHNNY HANNY; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2019)
The leader is a person who has the ability to influence individuals and groups to be able to work together toachieve predetermined goals. Leadership has an important role in the life of organizations and groups,namely to be able to move, empower, and direct resources effectively and efficiently towards the achievementof goals. The purpose of this study is to produce a picture of the magnitude of the influence of leadershipstyle on improving the economic development of rural communities in Koreng Village, Tareran District,South Minahasa Regency and to find out how the leadership style of village leaders can influence theincrease in economic development of rural communities in Koreng Village, Tareran District, SouthMinahasa Regency. The benefit of this research is that it can contribute useful knowledge and ideas andenrich knowledge and can be used as input for village governments to improve community economicdevelopment and evaluate knowledge. The results of this study indicate that the leadership style of the villagehead significantly influences the economic development of the community. And the village head in KorengVillage, Tareran Subdistrict, South Minahasa Regency, is more of a laisses faire leadership style In thistype of leadership the lessez faire the leader practically does not lead. He let his group and everyone do theirown way. In the sense that leaders who have the type of Leissez Faire only depend on their subordinateswithout joint decision making. Thus, to improve the economic development of the Koreng Village, TareranSubdistrict, South Minahasa Regency, it takes a leader who is able to serve and influence his community toinfluence, inspire, listen to community complaints and be able to provide motivation and set an example forhis community.Keywords: Leadership Style, Village Head, Increased Economic Development